A Molecular View of the Surface Pressure/Area Per Lipid Isotherms Assessed by FTIR/ATR Spectroscopy - Disalvo, Edgardo Anibal (2022)
The macroscopic behavior of a lipid monolayer in terms of packing and compressibility properties is classically obtained from surface pressure/area per molecule isotherms. Molecular interpretations trying to fit the II/A curves have been attempted by molecular dynamics. In this regard, the simulation is performed by introducing parameters accounting for the lipid-lipid interaction in the monolayer plane. However, water, as an essential component of the interfacial phenomena, is not explicitly included in terms of molecular arrays. This drawback appears to be a consequence of the lack of experimental evidence that may complement the macroscopic view with the microscopic features. In this work, we propose that II/A curves can be reproduced from microscopic molecular data obtained with FTIR/ATR spectroscopy. The changes in surface pressure, in fact, changes in the surface tension of the lipid–water interphase, can be related to the acyl regions exposed to water and evaluated by the ratio of isolated-to-connected CH2 populations. In turn, the area changes correspond to the variations in the primary and secondary hydration shells of the phosphate region. The isolated/connected CH2 ratio represents the extension of the non-polar region exposed to water and is linked to the resulting water surface tension. The area per lipid is determined by the excluded volume of the hydration shells around the phosphate groups in correlation to the carbonyl groups. The derivative of the frequencies of the -CH2 groups with respect to the water content gives an insight into the influence of water arrangements on the compressibility properties, which is important in understanding biologically relevant phenomena, such as osmotic stress in cells and the mechanical response of monolayers. It is concluded that the water population distributed around the different groups dominates, to a great extent, the physical properties of the lipid membranes.